Multifaceted Applications of Luminescent Metalloporphyrin Derivatives: Fluorescence Turn-On Sensing of Nicotine and Antimicrobial Activity - Mondal, Sourav; Ahmad, Imran; Dey, Nilanjan (ACS applied bio materials, 2024)
In this study, we designed and synthesized metalloporphyrin derivatives (with Ni and Zn) specifically intended for the fluorescence detection of nicotine in aqueous solutions. Our results showcased a notable selectivity for nicotine over other naturally occurring food toxins, exhibiting an exceptional sensitivity with a limit of detection as low as 7.2 nM. Through mechanistic investigations (1H NMR, FT-IR, etc.), we elucidated the binding mechanism, revealing the specific interaction between the pyridine ring of nicotine and the metal center, while the N atom pyrrolidine unit engaged in the hydrogen bonding with the side chain of the porphyrin ring. Notably, we observed that the nature of the metal center dictated the extent of interaction with nicotine; particularly, Zn-porphyrin demonstrated a superior response compared to Ni-porphyrin. Furthermore, we performed the quantitative estimation of nicotine in commercially available tobacco products. Additionally, we conducted the antibacterial (Staphylococcus aureus and Escherichia coli) and antifungal (Candida albicans) activities of the porphyrin derivatives.